A Preliminary Study of the Algicidal Mechanism of Bioactive Metabolites of Brevibacillus laterosporus on Oscillatoria in Prawn Ponds. (9th March 2014) - Jia, Wen; Huang, Xianghu; Li, Changling
Abstract : The algae, Oscillatoria, is commonly found in prawn ponds and can lead to reduced productivity. We examined metabolites of the bacteria Brevibacillus laterosporus for algicidal qualities. To determine the possible algicidal mechanisms of these bioactive metabolites, different amounts of sterile filtrate of bacterial suspensions were added to cultures containing Oscillatoria . The dry weight, the concentrations of chlorophyll-a (chl-a), phycobiliprotein (PC, phycocyanin; APC, allophycocyanin; PE, phycoerythrin), and MDA (malondialdehyde) and the activities of SOD (superoxide dismutase), POD (peroxidase), and CAT (catalase) of algae were measured during the algicidal application. The results showed that lower concentrations of the sterile filtrate (addition ≤ 4 mL) accelerated the growth rate of Oscillatoria, but significant inhibition and lysis were observed with higher concentrations (addition ≥ 8 mL). In two trials (the additions were 8 mL and 10 mL, respectively), the algal dry weights were reduced by 26.02% and 45.30%, and the chl-a concentrations were decreased by 46.88% and 63.73%, respectively, after seven days. During the algicidal treatment, the concentrations of PC, APC, PE, and MDA and the activities of SOD, POD, and CAT were significantly increased in the early cultivation and declined quickly at later stages. Finally, the algae-lysing mechanism of the bioactive metabolites of the bacteria Brevibacillus laterosporus on Oscillatoria had been proposed.